COVID-19, Middle Level Teacher Candidates, and Colloquialisms: Navigating Emergency Remote Field Experiences - Brooke B Eisenbach; Paula Greathouse; Caroline Acquaviva (Middle Grades Review, 2020)
COVID-19 challenged teacher educators and teacher candidates in ways we could have never imagined. Colloquialisms regarding the move from educator preparation to practice shifted from common truths to dynamic considerations in light of the pandemic and transition to emergency remote teaching and learning. In this essay, we share our experiences working with middle level teacher candidates during the COVID-19 pandemic. We identify the ways in which our teacher candidates rose to the challenge and demonstrated critical thinking, creativity and compassion beyond our prior expectations of rising middle level educators amidst a time of unprecedented change and uncertainty.
Keywords: teacher candidate; middle level; early adolescent; teacher preparation; COVID-19; pandemic pedagogy